2013
DOI: 10.1097/dbp.0b013e3182a50a67
|View full text |Cite
|
Sign up to set email alerts
|

ADHD Is a Risk Factor for Overweight and Obesity in Children

Abstract: Objective Although hyperactivity would seem to increase energy expenditure, attention deficit/hyperactivity disorder (ADHD) appears to increase the risk for being overweight. The present study examined the Body Mass Index (BMI) in children with ADHD and its relationship with age, gender, ADHD and comorbid symptom severity, inhibitory control, developmental coordination disorder (DCD), sleep duration and methylphenidate use. Method Participants were 372 Dutch children with ADHD combined type aged 5–17 years p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 29 publications
5
67
1
6
Order By: Relevance
“…61 Similar to those with BD, adolescents with ADHD are also more likely to be overweight or obese. 62 Part of this association may be explained by individuals with ADHD eating impulsively possibly being more likely to binge-eat. 63 …”
Section: Adhd × Bmi Interaction In Patients With Bdmentioning
confidence: 99%
“…61 Similar to those with BD, adolescents with ADHD are also more likely to be overweight or obese. 62 Part of this association may be explained by individuals with ADHD eating impulsively possibly being more likely to binge-eat. 63 …”
Section: Adhd × Bmi Interaction In Patients With Bdmentioning
confidence: 99%
“…Interestingly, non-medicated children diagnosed with ADHD have a 1.5-fold increased risk of becoming overweight relative to control subjects [17]. Studies have also revealed high rates of ADHD in patients seeking weight loss treatment (26-61 %), suggesting an association between ADHD and obesity [18].…”
Section: Obesity and Adhdmentioning
confidence: 99%
“…Age effects have rarely been tested directly, but when they were, differential age effects were reported. For example, two studies (Fliers et al, 2013; A. W. van Egmond-Fröhlich et al, 2012) found that effects were smaller in younger than older children, although Fliers et al found a curvilinear effect with age.…”
Section: Introductionmentioning
confidence: 99%